Phenotypic Variation for Root Distribution of IR64, KDML105 and KDML105 Mutant Rice Varieties in Water Deficit and Well-Watered Conditions - Jaruwatee, Sorathan; Supaibulwatana, Kanyaratt; Cha-um, Suriyan; Saengwilai, Patompong (Science Essence Journal, 2019)
ABSTRACT Phenotypic variation for root distribution is associated with the ability of plants to acquire water and nutrients available at different soil strata. Rice production is known to be susceptible to water deficit stress (WS) because rice requires much water for cultivation. In this study, we explored natural variation of root distribution among IR64, KDML105 and KDML105 mutant lines (MT1, MT2, MT3) derived from gamma irradiation combined with ethyl methane sulfonate treatment. Plants were grown in a root basket and a root box system. We found that KDML105 had lower root to shoot ratio (27.49%) and less rooting depth (27.25%) compared to IR64. In the root box system, we found that WS decreased an average shoot biomass by 32.9%. The mutant lines maintained their shoot mass under WS while that of KDML105 was significantly reduced. Physiological analysis revealed that MT2 had the lowest evapotranspiration rate of 76.6%. In addition, MT2 and MT3 increased photosynthetic pigments under WS. KDML105 increased its rooting depth while MT1 and MT2 reduced rooting depth by 17.5% and 15.2%, respectively, under WS. Root distribution was associated with crown root number per tiller but not necessary with water use efficiency in our system. Keywords: Rice, Root, Root distribution, Water deficit, Mutant rice